2016
DOI: 10.1038/nplants.2016.76
|View full text |Cite
|
Sign up to set email alerts
|

The upside-down water collection system of Syntrichia caninervis

Abstract: Researchers have revealed minuscule features on the leaves of a common desert plant that allow it to collect water from moist air. © 2 0 1 6 M a c m i l l a n P u b l i s h e r s L i m i t e d. A l l r i g h t s r e s e r v e d .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
128
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(129 citation statements)
references
References 23 publications
1
128
0
Order By: Relevance
“…Our observations of a gradual decrease in the total BC and BR across the grazing gradient regardless of aridity conditions are similar to those reported by Concostrina-Zubiri et al (2014) and Eldridge et al (2015), who found a reduction in BC across grazing gradients in drylands of Mexico and Australia, respectively. And mosses can recover from trampling by sheep relatively fast if damage is only partial because, as poikilohydric organisms, they have developed specialized leaf structures to collect water from many available sources (Pan et al, 2016). At HG conditions we observed a high relative abundance of LI, and even a positive effect of HG conditions on lichens in this site.…”
Section: Grazing Interacts With Aridity To Determine Biocrust Biomamentioning
confidence: 66%
See 1 more Smart Citation
“…Our observations of a gradual decrease in the total BC and BR across the grazing gradient regardless of aridity conditions are similar to those reported by Concostrina-Zubiri et al (2014) and Eldridge et al (2015), who found a reduction in BC across grazing gradients in drylands of Mexico and Australia, respectively. And mosses can recover from trampling by sheep relatively fast if damage is only partial because, as poikilohydric organisms, they have developed specialized leaf structures to collect water from many available sources (Pan et al, 2016). At HG conditions we observed a high relative abundance of LI, and even a positive effect of HG conditions on lichens in this site.…”
Section: Grazing Interacts With Aridity To Determine Biocrust Biomamentioning
confidence: 66%
“…Crustose and squamulose morphologies, such as those found in this site, can provide lichens with partial resistance to mechanical impact (Concostrina-Zubiri et al, 2014;Jiménez Aguilar et al, 2009). And mosses can recover from trampling by sheep relatively fast if damage is only partial because, as poikilohydric organisms, they have developed specialized leaf structures to collect water from many available sources (Pan et al, 2016). LI and MS present higher chl a contents by surface unit than cyanobacteria-dominated biocrusts (Lan et al, 2012).…”
Section: Grazing Interacts With Aridity To Determine Biocrust Biomamentioning
confidence: 85%
“…Thus, dramatic mortality of this common moss, which is one of the most abundant desert mosses in the world16, was observed with both increased temperature and altered precipitation treatments. Significant responses due to warming and watering + warming were also seen in reduced cover of the dominant lichens ( Collema tenax and Collema coccophorum )9.…”
mentioning
confidence: 99%
“…After a period, more water was appeared in the nanogrooves and eventually filled the microgrooves (Figure d–f). Moreover, based on further ESEM observations, they also revealed the mechanisms of water collection from limited water sources and transportation on the mosses, and presented the physics‐based evidence of how bryophytes adapt to scarce water environments by efficiently using their small structures …”
Section: Recent Applicationsmentioning
confidence: 95%
“…The scale bar in (a) also applies to (b–f). Reproduced with permission . Copyright 2016, Springer Nature.…”
Section: Recent Applicationsmentioning
confidence: 99%